Fisher-Shannon analysis of the São Francisco river flow: the influence of dams and reservoirs (Research, Society and Development, 2020)
We investigated how the construction of the Sobradinho and Xingó dams affected the daily streamflow of the São Francisco River, using Fisher - Shannon analysis. The daily streamflow time series of the fluviometric stations Juazeiro / BA and Pão de Açúcar / AL that are located downstream of the Sobradinho and Xingó reservoirs were analyzed for the periods prior to the construction of both reservoirs, after the construction of Sobradinho and before the construction of Xingó, and after the construction of both reservoirs. We applied Fisher-Shannon analysis to streamflow subseries and in moving windows, evaluating differences using the Kruskal-Wallis test. This method simultaneously quantifies the local and global properties of the probability density function of the analyzed signal. We observed that in the natural regime the degree of temporal organization of the streamflow series decreased with an increase in the drainage area. After the construction of Sobradinho the degree of regularity of the streamflow dynamics decreased comparing to the natural regime and after the construction of Xingó we observed a more regular and more organized streamflow dynamics. Thus, the operations of the reservoirs changed the degree of regularity and temporal organization of the streamflow series, as indicated by the entropy and Fisher information values, respectively.